Assessing effectiveness of drought tolerance indices in selecting grape (Vitis vinifera) under induced drought stress conditions - PRAKASH, JAI; S, AMULYA; VERMA, M K; SINGH, SANJAY K; BHARADWAJ, C; THAKRE, MADHUBALA; KUMAR, CHAVLESH; C J, YOGESH BABU (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during 2021–23 at ICAR-Indian Agricultural Research Institute, New Delhi, focusing on 10 diverse grape (Vitis vinifera L.) genotypes [Pusa Navrang (PN), Pusa Aditi (PA), Pusa Trisha (PT), Pusa Swarnika (PS), Pusa Purple Seedless (PPS), Flame Seedless (FS), St. George (SG), Dog Ridge (DR), V. parviflora (VP), and Male Hybrid (MH)] for their response to controlled moisture stress (21 days) and well-watered conditions in plastic pots (14) maintained under polyhouse conditions. Drought decreased plant height differently among genotypes (9.71–41.68%). Dogridge had the highest root: shoot ratio (0.79), St. George showed lower (0.44) in response to drought. Drought tolerance indices identified genotypes Vitis parviflora (VP), Pusa Navrang (PN), Male Hybrid (MH) and Dogridge (Vitis × champini) (DR) as more drought-tolerant, while Pusa Trishar (PT) and Flame Seedless (FS) were susceptible. Cluster analysis showcased distinct differences among genotypes, while principal component analysis (PCA) emphasized key indices predicting performance in varying conditions with 98.91% variance for plant height and 99.10% variance for index root: shoot ratio contributed from two primary principal components (PC1 and PC2). Correlations (P